Multi-omics analysis provides insights into the mechanism underlying fruit color formation in Capsicum - Song, Zhao; Xu, Xiaowan; Chen, Xiao; Chang, Jingjing; Li, Jing; Cheng, Jiaowen; Zhang, Baige (Frontiers in Plant Science, 2024)
Fruit color is a crucial attribute of fruit quality in peppers (Capsicum spp.). However, few studies have focused on the mechanism of color formation in immature pepper fruits. In this study, the lightyellow color observed in immature CSJ009 fruits compared to CSJ010 could be attributed to decreased chlorophyll and carotenoid pigments. Through integrated analysis of the transcriptome and metabolome of CSJ009 and CSJ010, we identified 23,930 differentially expressed genes (DEGs) and 345 differentially accumulated metabolites (DAMs). Furthermore, integrated analysis revealed a strong correlation between the HCT-like gene and metabolite MWS0178 (chlorogenic acid). Paraffin section assay revealed that the epidermal cells of immature CSJ010 fruits exhibited a more compact arrangement with significantly greater length than those of CSJ009. Quantitative determination of carotenoids showed that lutein emerged as the predominant carotenoid in immature pepper fruits.Additionally, missense mutation of LCYB2 is likely to lead to a decrease in β-carotene content in immature CSJ009 fruits, whereas CCS may directly catalyze the conversion of lycopene to β-carotene in mature fruits. The null mutation in CCS promoted the biosynthesis of β,ε-branch carotenoids leading to lutein being the most abundant carotenoid found in orange CSJ010 fruits. These findings provide important insights into the mechanism underlying color formation in pepper fruits and establish a foundation for the further exploration of color-related genes.